2010
DOI: 10.1063/1.3368689
|View full text |Cite
|
Sign up to set email alerts
|

Small valence-band offset of In0.17Al0.83N/GaN heterostructure grown by metal-organic vapor phase epitaxy

Abstract: The valence-band offset of a lattice-matched In0.17Al0.83N/GaN heterostructure grown by metal-organic vapor phase epitaxy (MOVPE) was investigated by x-ray photoelectron spectroscopy (XPS). Atomic force microscopy and angle-resolved XPS indicated that a thin In0.17Al0.83N (2.5 nm) layer was successfully grown by MOVPE on GaN. The XPS result showed that the valence band offset was 0.2±0.3 eV. This result indicates that the conduction-band offset at the In0.17Al0.83N/GaN interface is large, i.e., 0.9 to 1.0 eV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…7 For GaN, E CNL is reported to be 2.4 eV above the valence band edge E V . 6 By considering the valence band offset DE V at the InAlN/GaN interface measured to be 0.2 eV in our previous study, 8 E CNL for In 0.17 Al 0.83 N is estimated to be at 2.6 eV above E V , i.e., 2.0 eV below E C . To clarify this relation, band alignment among Al 2 O 3 , InAlN, and GaN is schematically illustrated with E CNL in Fig.…”
Section: -2mentioning
confidence: 99%
“…7 For GaN, E CNL is reported to be 2.4 eV above the valence band edge E V . 6 By considering the valence band offset DE V at the InAlN/GaN interface measured to be 0.2 eV in our previous study, 8 E CNL for In 0.17 Al 0.83 N is estimated to be at 2.6 eV above E V , i.e., 2.0 eV below E C . To clarify this relation, band alignment among Al 2 O 3 , InAlN, and GaN is schematically illustrated with E CNL in Fig.…”
Section: -2mentioning
confidence: 99%
“…2, where E C is the conduction-band minimum, E V is the valence-band maximum ͑VBM͒, and E F indicates Fermi level that is set to the origin of binding energy in XPS measurement. In our preliminary work, 13 we used the In 4d spectrum that overlapped with the Ga 3d and N 2s spectra very closely on both sides. The Al 2p spectrum, however, does not overlapped with any other spectra and is therefore more suitable for the ⌬E V measurement.…”
Section: Theory Of Measurementmentioning
confidence: 99%
“…However, evaluating ⌬E V by using XPS is possibly erroneous due to sharp band bending caused by the spontaneous and piezoelectric polarization in ultrathin InAlN layers. In our preliminary work, 13 the ⌬E V of lattice-matched In 0.17 Al 0.83 N / GaN grown by metal-organic vapor phase epitaxy ͑MOVPE͒ was evaluated correctly by taking into account band bending due to the polarization-induced electric field combined with surface Fermi-level pinning. In addition to the lattice-matched In 0.17 Al 0.83 N / GaN heterostructure, the pseudomorphic heterostructures of In 0.25 Al 0.75 N / GaN and In 0.30 Al 0.70 N / GaN were also grown and characterized in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy study showed that the HF treatment is effective in reducing native oxides at the GaN-based alloys. 26,27 Ohmic contacts were ring-shaped Ti/Al/Ti/Au multilayers and gate contacts were either Al/Au or Ni/Au circles with diameters from 200 to 500 lm. An ohmic annealing was carried out at 830 C for 2 min in N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The HF treatment was chosen as more efficient in removal of native oxides compared to other treatments using hydrochloric acid or ammonium hydroxide in the case of InAlN and GaN. 26,27 The applied chemical approach was realized by dipping the sample in the HF solution for 1 min at RT, then rinsing it in deionized water, followed by a blowing process with pure nitrogen. The X-ray photoelectron spectroscopy study showed that the HF treatment is effective in reducing native oxides at the GaN-based alloys.…”
Section: Introductionmentioning
confidence: 99%